Computed tomography hypoperfusion-hypodensity mismatch vs. automated perfusion mismatch to identify stroke patients eligible for thrombolysis - Sporns, Peter B.; Kemmling, André; Meyer, Lennart; Krogias, Christos; Puetz, Volker; Thierfelder, Kolja M.; Duering, Marco; Lukas, Carsten; Kaiser, Daniel; Langner, Sönke; Brehm, Alex; Rotkopf, Lukas T.; et al. (Frontiers in Neurology, 2023)
Background and Purpose: Automated perfusion imaging can detect stroke patients suitable for thrombolysis with unknown time of symptom onset. However, availability of this technique is limited. We therefore established the novel concept of computed tomography (CT) hypoperfusion-hypodensity mismatch, i.e. an ischemic core lesion visible on cerebral perfusion CT without visible hypodensity in corresponding native cerebral CT. We compared both methods regarding their accuracy to identify patients suitable for thrombolysis.In a retrospective analysis of the MissPerfeCT observational cohort study, patients were classified as suitable or not for thrombolysis based on established time window-and imaging-criteria. We calculated predictive values for hypoperfusion-hypodensity mismatch and automated perfusion imaging to compare accuracy in identification of patients suitable for thrombolysis.Of 247 patients, 219 (88.7%) were and 28 (11.3%) were not eligible for thrombolysis. Of 197 patients within 4.5 hours of symptom onset, 190 (96.4%) were identified by hypoperfusionhypodensity mismatch and 88 (44.7%) by automated perfusion mismatch (P<0.001). Of 22 patients beyond 4.5 hours, but suitable for thrombolysis, 5 (22.7%) were identified by hypoperfusionhypodensity mismatch. Predictive values for the hypoperfusion-hypodensity mismatch vs. automated perfusion mismatch were as follows: sensitivity 89.0% vs. 50.2%, specificity 71.4% vs. 100.0%, positive predictive value 96.1% vs. 100.0%, negative predictive value 45.5% vs. 20.4%.The novel method of hypoperfusion-hypodensity mismatch can identify patients suitable for thrombolysis with higher sensitivity and lower specificity than established techniques. Using this simple method might therefore increase the proportion of patients treated with thrombolysis without the use of special automated software.The MissPerfeCT study is a retrospective observational multicenter cohort study and is registered with clinicaltrials.gov (NCT04277728).